New insights into the role of microheterogeneity of ZP3 during structural maturation of the avian equivalent of mammalian zona pellucida - Okumura, Hiroki; Mizuno, Ayaka; Iwamoto, Eri; Sakuma, Rio; Nishio, Shunsuke; Nishijima, Ken-ichi; Matsuda, Tsukasa; Ujita, Minoru (PLOS ONE, 2023)
The egg coat including mammalian zona pellucida (ZP) and the avian equivalent, i.e., inner-perivitelline layer (IPVL), is a specialized extracellular matrix being composed of the ZP glycoproteins and surrounds both pre-ovulatory oocytes and ovulated egg cells in vertebrates. The egg coat is well known for its potential importance in both the reproduction and early development, although the underlying molecular mechanisms remain to be fully elucidated. Interestingly, ZP3, one of the ZP-glycoprotein family members forming scaffolds of the egg-coat matrices with other ZP glycoproteins, exhibits extreme but distinctive microheterogeneity to form a large number of isoelectric-point isoforms at least in the chicken IPVL. In the present study, we performed three-dimensional confocal imaging and two-dimensional polyacrylamide-gel electrophoresis (2D-PAGE) of chicken IPVLs that were isolated from the ovarian follicles at different growth stages before ovulation. The results suggest that the relative proportions of the ZP3 isoforms are differentially altered during the structural maturation of the egg-coat matrices. Furthermore, tandem mass spectrometry (MS/MS) analyses and ZP1 binding assays against separated ZP3 isoforms demonstrated that each ZP3 isoform contains characteristic modifications, and there are large differences among ZP3 isoforms in the ZP1 binding affinities. These results suggest that the microheterogeneity of chicken ZP3 might be regulated to be associated with the formation of egg-coat matrices during the structural maturation of chicken IPVL. Our findings may provide new insights into molecular mechanisms of egg-coat assembly processes.